RELATIONSHIP BETWEEN FUNCTIONAL INDICES OF MYOCARDIAL REMODELING AND BLOOD PRESSURE IN ATHLETES WITH PREHYPERTENSION - Ataman, Y.O.; Brizhata, I.A.; Lychko, V.S.; Oleshko, T.M.; Pryimenko, L.V.; Volnushkina, N.Y. (World of Medicine and Biology, 2024)
It was found that athletes with prehypertension have a higher parameter of left ventricular hypertrophy Romhilt-Estes index, according to other parameters (Sokolov-Lyon index, Cornell voltage index, Gubner index, Perugia index, prevalence of arrhythmias and early ventricular repolarization syndrome) no differences were found. Echocardiogram analysis revealed a significant increase of the left ventricular myocardium mass index: 103.73±18.93 g/m2 for prehypertensive athletes and 86.70±20.55 g/m2 for the persons with normal optimal blood pressure; р=0.012), Tei index did not differ strongly between both groups. We also found a moderate positive correlation between pulse blood pressure and Romhilt-Estes index, r = 0.745, p
Keywords: myocardial remodeling; electrocardiography; blood pressure; professional athletes; prehypertension